Sistem Pendidikan Di Malaysia Era Kontemporer:Penguatan Nilai-Nilai Religius - Usama, Danil; Sassi, Komarudin; Noviani, Dwi (STAI Denpasar Bali, 2023)
The purpose of Islam education is to form Muslim personal that develop spiritual, physical, emotional intellectual and social potensials. It does not only produces good citizens but also covers the formation of a complete human capital in terms of religious and worldly life. In addition, The goal of Islamic education not only to produce good person but also the persons who that can meet the needs of the world and life in the hereafter. The main focus of this article is about the development of Islamic Education in Malaysia include the type and level of education, and education policy in contemporary this era.